Contrasting Winter Versus Summer Microbial Communities and Metabolic Functions in a Permafrost Thaw Lake - Vigneron, Adrien; Lovejoy, Connie; Cruaud, Perrine; Kalenitchenko, Dimitri; Culley, Alexander; Vincent, Warwick (Frontiers in Microbiology, 2019)
International audience